2000
DOI: 10.7863/jum.2000.19.12.837
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic septation: a useful prognostic indicator of acute thoracic empyema.

Abstract: The aim of this study was to identify sonographic predictors of patient outcomes or need for surgical intervention of acute thoracic empyema. All patients with a clinical diagnosis of thoracic empyema underwent transthoracic ultrasonographic examination and thoracentesis at admission. According to the presence or absence of septa in sonographic images, the patients were classified into two groups: septated and nonseptated. Sonographic findings were analyzed with respect to duration of hospital stay, chest tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 18 publications
1
67
0
1
Order By: Relevance
“…3) has clinical implications. Several studies have shown that patients with septated effusions needed longer chest tube drainage, longer hospital care and were more likely to require fibrinolytic therapy or surgery compared to those with non-septated effusions [18,19].…”
Section: Pleural Pathology Pleural Effusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) has clinical implications. Several studies have shown that patients with septated effusions needed longer chest tube drainage, longer hospital care and were more likely to require fibrinolytic therapy or surgery compared to those with non-septated effusions [18,19].…”
Section: Pleural Pathology Pleural Effusionsmentioning
confidence: 99%
“…Moreover, the risk of pneumothorax following aspirations is reduced, irrespective of the size of the effusion [21]. Depending on operator experience, ultrasonography may also guide further decisions regarding the need for tube drainage, intrapleural fibrinolytic therapy, pleuroscopy or surgical intervention [22].…”
Section: Pleural Pathology Pleural Effusionsmentioning
confidence: 99%
“…As reported, tuberculous pleural effusions and empyema commonly had complex septated sonographic appearances. 6,[13][14][15] However, the differentiation between empyema and tuberculosis is easily made. Therefore, our objective was to focus on the lymphocyte-rich exudative pleural effusions.…”
Section: D a Bmentioning
confidence: 99%
“…Existing data are mixed. In an unblinded trial, the presence of sonographic septations was predictive of more aggressive treatment, but did not specifically address the success or failure of tube drainage in this population (19).…”
Section: Thoracic Chest Tube Placementmentioning
confidence: 98%